A Case of Dermatitis Herpetiformis With Fibrillar Immunoglobulin A Deposition: A Rare Pattern Not to Be Missed. (July 2019) - Lilo, Mohammed T.; Yan, Shaofeng; Chapman, Michael S.; Linos, Konstantinos
Abstract : Abstract: Dermatitis herpetiformis is a rare, chronic autoimmune disorder characterized by intense pruritic papules and vesicles, which can be associated with celiac disease and other autoimmune disorders. Its histologic characteristic is the accumulation of neutrophils within the papillary dermis with granular deposition of immunoglobulin A (IgA) observed under direct immunofluorescence. Herein, we report a 58-year-old woman who presented with a vesicular rash on the buttocks. The patient reported a recent history of genital herpes, Entamoeba histolytica colitis, recurrent hives, and eczema. A representative biopsy demonstrated features of spongiotic dermatitis and focal papillary dermal neutrophilic aggregates. Direct immunofluorescence revealed fibrillary IgA deposition in the papillary dermis, granular C3 deposition at the dermal–epidermal junction, and dermal papillae. The overall clinical, histologic, and DIF findings were consistent with those of dermatitis herpetiformis. The fibrillar IgA pattern is rare and easily overlooked by the unwary. Pathologists should be aware of this rare pattern, especially when the histologic findings are not classic.